2009
DOI: 10.1111/j.1442-2018.2009.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver suctioning education for Japanese patients with an invasive home ventilator

Abstract: In Japan, more people require care activities at home. In particular, patients with an invasive mechanical ventilator in the home require extensive care by family caregivers. Collaboration between their nurses and paid caregivers in the provision of care activities, especially tracheal suctioning, is necessary. This three-round Delphi study identifies the essential items required by nurses to instruct the paid caregivers in how to carry out tracheal suctioning on patients with an invasive mechanical ventilator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…The search strategy allowed retrieving articles between 1999 and 2013; three of the five articles were published within the last four years (Donley, Chan, & Webber, ; Imaiso & Yamauchi, ; Tredinnick & Cocks, ). One article was published in early 2000's (Chadwick, Jolliffe, & Goldbart, ) and one late 1990's (Sterrick & Foley, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The search strategy allowed retrieving articles between 1999 and 2013; three of the five articles were published within the last four years (Donley, Chan, & Webber, ; Imaiso & Yamauchi, ; Tredinnick & Cocks, ). One article was published in early 2000's (Chadwick, Jolliffe, & Goldbart, ) and one late 1990's (Sterrick & Foley, ).…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies provided a comprehensive up‐to‐date literature review, the methodology was identified, and the rationale for undertaking the research clearly outlined. However, ethical considerations were only mentioned in two of the five articles (Imaiso & Yamauchi, ; Tredinnick & Cocks, ). None of the papers were excluded due to poor quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HMV 적용 환자의 실태 [4], 관련장비의 효용성 [8], 건강상태에 대한 영향요인과 다학제 접근의 효과 [10][11][12][13][14], HMV 적용 환자 에 관한 체계적 고찰과 가이드라인 제시 [15][16][17] 등 다양한 형태 로 많은 연구들이 보고되고 있다. 그러나 국내에서는 HMV 적 용 환자와 관련한 실태조사 [6,18], 삶의 질과 재입원의 영향요 인 [7,19] Table 1).…”
Section: 그동안 Hmv 적용 환자와 관련된 국외 연구를 살펴보면unclassified